STUDI TENTANG FI’IL AMAR - LUBIS, ALI ASRUN (IAIN Padangsidimpuan, 2014)
Fi’il Amar is a command verb, command from who has highest position to the lowest position. There are many kinds command verbs in Arabic. It means that it is not only one word that used to do command or order. Types amar are do’a, iltimas, irsyad, tahdid, ta’jiz, takwin, ta’dis and ta’ajjub. And the meaning amar is not only in command and order, but the aim for request, ask, permit choose, instruction, to weaken, intimidation, hope, future and so on. But the original meaning is obligated and ordered.